High-density cervical ureaplasma urealyticum colonization in pregnant women - Ranđelović Gordana; Kocić Branislava; Miljković-Selimović Biljana; Mladenović-Antić Snežana; Stojanović Predrag; Stefanović Milan (Vojnosanitetski Pregled)
Background/aim: Ureaplasma urealyticum, a common commensal of the female lower genital tract, has been observed as an important opportunistic pathogen during pregnancy. The aims of this study were to determine the degree of cervical colonization with U. urealyticum in pregnant women with risk pregnancy and in pregnant women with normal term delivery and to evaluate the correlation between high-density cervical U. urealyticum colonization and premature rupture of membranes (PROM) as well. Methods. This research was conducted on the samples comprising 130 hospitalized pregnant women with threatening preterm delivery and premature rupture of membranes. The control group consisted of 39 pregnant women with term delivery without PROM. In addition to standard bacteriological examination and performing direct immunofluorescence test to detect Chlamydia trachomatis, cervical swabs were also examined for the presence of U. urealyticum and Mycoplasma hominis by commercially available Mycofast Evolution 2 test (International Microbio, France). Results. The number of findings with isolated high-density U. urealyticum in the target group was 69 (53.08%), while in the control group was 14 (35.90%). Premature rupture of membranes (PROM) occurred in 43 (33.08%) examinees: 29 were pPROM, and 14 were PROM. The finding of U.urealyticum ≥104 was determined in 25 (58.14%) pregnant women with rupture, 17 were pPROM, and 8 were PROM. There was statistically significant difference in the finding of high-density U. urealyticum between the pregnant women with PROM and the control group (χ² = 4.06, p < 0.05). U. urealyticum was predominant bacterial species found in 62.79% of isolates in the PROM cases, while in 32.56% it was isolated alone. Among the 49 pregnant women with preterm delivery, pPROM occurred in 29 (59.18%) examinees, and in 70.83% of pregnant women with findings of high-density U. urealyticum pPROM was observed. Conclusion. Cervical colonization with U. urealyticum ≥ 104 is more frequent in pregnant women with risk pregnancy than in pregnant women with normal term delivery. High-density cervical U. urealyticum colonization should be observed as a possible etiological factor for PROM.